THE EFFECTIVENESS OF USING CONVERSATION VIDEO ENTITLED “APOLOGY” TO IMPROVE STUDENTS’ PRONUNCIATION ABILITY THE CASE OF TENHT YEAR SMA N 1 JEPARA - Yusuf Bahtiar (Universitas PGRI Semarang, 2013)
The main objectives of this research are: (1) To know there are effectiveness or not of improving students’ pronunciation ability taught without using conversation video entitled “apology” (2) To know there are effectiveness or not of improving students’ pronunciation ability taught using conversation video entitled “apology” (3) to find out whether there is or not significant difference of the effectiveness of improving students’ pronunciation ability taught without using conversation video entitled “apology” and taught using conversation video entitled “apology”. This study is pre experimental research. The population of the research is 300 students of the tenth grade students of SMA N 1 Jepara 2012/2013. The writer took 30 students from oneclass. The instrument of this research is spoken test. The writer gave the students pre test, treatments and post-test. The treatment is that the students were taught by using conversation video entitled “apology”.The research result is that the mean of score post-test class (71,53) is higher than score pre test class (62,33). The writer used T-test formula to know the differences of pre test and post class score. The result of t-test is 12,16 and the t-table of 30 students is 1.967. The value of T-table is lower than T-test, so it can be concluded that there is a significant improvement of student’s pronunciation ability taught using conversation video entitled “apology”of tenth grade students of SMA N 1 Jepara.